Surface vs. Air Shipment of Humanitarian Goods under Demand Uncertainty. Issue 5 (1st March 2018) - Park, John H.; Kazaz, Burak; Webster, Scott
Abstract : The combination of insufficient funds and limited information regarding the demand in regions of desperate need presents a great challenge to many humanitarian organizations. This study examines how a humanitarian organization can minimize the expected shortage in delivering relief aid to regions of need, either though surface or air transportation, in the presence of demand uncertainty with a budget constraint. The study makes four contributions. First, we show that when there is reserved supply for air transportation, it is optimal to provide a higher service level through surface shipment to regions with greater demand uncertainty. Second, we show that the demand variation plays a significant role in the allocation of funds between surface and air shipments. The reaction of the humanitarian organization to higher degrees of demand uncertainty can be determined by the optimal level of inventory purchased for surface shipment. If the optimal inventory for surface shipment is less than the mean demand, then we show that increasing degrees of demand uncertainty leads to increasing reliance on the air shipment option with greater levels of inventory reserved for air transportation and decreasing levels of inventory reserved for surface shipment. Third, when there are opportunities to invest in better forecasting, we find that a humanitarian organization should focus its resources on improving the demand forecast in one region as opposed to evenly allocating resources to all regions. Fourth, we show that the expected amount of shortages reduces with a higher number of regions to serve due to a risk‐pooling effect.